Development of competition tactics using video clip DB for Korean Greco-Roman wrestlers in London 2012 Summer Olympics - Choi, K.-J.; Jing, D.-S.; Bang, D.-D. (Asian Conference on sport science. Sport science and elite training programme for world class performance. 25-26 October 2013. Hong Kong Sports Institute, Hong Kong, China, 2013)
This study was conducted for Korean national Greco-Roman style wrestlers to enhance their performance and to grasp gold medals in 2012 London Olympic Games through providing competition strategies using the analyses of the video clips of foreign competitive wrestlers. Three weight categories (55, 60, 66 kg) among seven in Greco-Roman style wrestling were selected, and top eight foreign wrestlers at each category were included. The video clips (n=228) of each category were gathered by converting AVA, and MP4 signals of the World Wrestling Championship, the Olympic Wrestling Quarter Games, the Asia and Europe Wrestling Championship, and Asian Games to WMV digital signals using KISS Archive system. Qualitative variables such as the posture of standing on the mat and parterre attack and defense, habits, weak point etc. as well as quantitative variables such as the number of success and fail in parterre attack and defense, score earned and lost, the frequency of important skills etc. were analyzed. National wrestling team coaches and the principle investigator developed the competition strategies, and objectified them by discussing the contents with five wrestling specialists twice. Competition strategies were modified through practice games under simulated conditions, and then trained to master them. After London Olympics, competition strategies were evaluated by analyzing the games which Korean wrestlers had with the foreign competitive wrestlers. Video clips could be useful for analyzing the games of competitive athletes qualitatively as well as quantitatively. They can be easily accessed with the smart phones to be acquainted with their style and habits. With these assistances Korea national wrestling team could bring up the self-confidence to win the games and psychological peace from the knowledge of competitive athletes' information.